Síntese, caracterização e eletrodeposição de monômeros baseados em 2,5-(Ditienil) Pirrol (SNS) ligados a derivados de dansila e fluoreno - Lima Neto, Jorge de (2020)
The synthesis of conjugated polymers has aroused great scientific and commercial interest due to their electrical and optoelectronic properties, making them applicable in the development of optoelectronic devices. Such properties can be achieved by structural modification of the starting monomer and the introduction of fluorescent molecules in their structure may lead to the formation of conjugated polymers with electrochromic and/or fluorescent properties. Among the various monomers described in the literature, 2,5-di(thienyl)pyrrol (SNS) derivatives have attracted great deal of attention due to the good optoelectronic properties that their polymers may show. In the present work, the synthesis of two new SNS monomers bearing a dansyl (SNS-D) and fluorene (SNS-FCA) moiety were achieved in good yields, having their structures characterized by 1H, 13C Nuclear Magnetic Resonance experiments, Fourier Transform Infrared Spectroscopy (FTIR), High Resolution Mass Spectrometry, melting point, UV-Vis / NIR and fluorescence. Electrochemical polymerization experiments were conducted by the cyclic voltammetry method in a 0.1 mol L-1 CH3CN/(C4H9)4NBF4 system. The SNS-D monomer was copolymerized in the presence of 3,4-ethylenedioxythiophene (EDOT) leading to the formation of Poly(SNS-D-co-EDOT) in a potential range of 0.0 V ≤ E ≤ 0.85 V. The polymeric film showed electrochromic behavior, varying its coloration between green in neutral state and dark blue in oxidized state. The spectroelectrochemical characterization showed high absorption in the near infrared region (1040 nm), with chromatic contrast (Δ%T) of 27% in the first cycle and 17% in the 600th cycle and response time of 3 to 4 seconds between redox states. While electrochemical polymerization of the SNS-FCA monomer led to the formation of Poly(SNS-FCA) in a potential range of 0.0 V ≤ E ≤ 0.65 V, also presenting electrochromic behavior, varying its coloration between shades of green and blue in its neutral and oxidized states, respectively. Spectroelectrochemical experiments revealed high absorption at 1030 nm with Δ% T of 41% in the first cycle and 11% in the 500th cycle, and a response time of 10 and 30 seconds between redox states. These observed properties suggest that the polymers obtained in this work may be promising to act as an active layer in optoelectronic devices such as smart windows.